2010
DOI: 10.4028/www.scientific.net/amr.133-134.65
|View full text |Cite
|
Sign up to set email alerts
|

The Conservation of Earthen Architectural Heritage in Seismic Areas

Abstract: The acceleration of climate change and the increasing frequency of natural disasters mean that there is an urgent need to adapt conservation strategies for architectural heritage to the world’s new demands and situations. This is particularly relevant for the most vulnerable constructions, such as earthen structures. Because of the dramatic effect that earthquakes can have on architecture, and especially on historical monuments, they have been studied for the past 50 years. Earthquakes divide the world in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Usually in the engineering community, the expression conservation of adobe architecture in seismic-prone regions is not commonly used. There are a few references regarding historical earthen buildings in seismic areas with the title of "conservation of earthen architecture heritage" (Montes, Giesen, 2010;Vargas-Neumann, 2012). In Terra Literature Review, "Earthen Material Conservation" (Oliver, 2008) and "Seismic Damage of Earthen Structure" (Webster, 2008) have been embraced separately in different chapters.…”
Section: First Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually in the engineering community, the expression conservation of adobe architecture in seismic-prone regions is not commonly used. There are a few references regarding historical earthen buildings in seismic areas with the title of "conservation of earthen architecture heritage" (Montes, Giesen, 2010;Vargas-Neumann, 2012). In Terra Literature Review, "Earthen Material Conservation" (Oliver, 2008) and "Seismic Damage of Earthen Structure" (Webster, 2008) have been embraced separately in different chapters.…”
Section: First Questionmentioning
confidence: 99%
“…Professionals often study just the physical aspect of earthen architecture (Blondet, Aguilar, 2007;Minke, 2001;Morris, Walker, Drupsteen, 2011;Tolles et al, 2000;Torrealva, Vargas-Neumann, Blondet, 2006;UNIPD, 2012;Webster, 2008). There is very little research that deals with principles addressing conservation of earthen architectural heritage in a seismic region (Correia, Walliman, 2014), and no relevant intervention techniques have been considered (Vargas-Neumann, 2012;Vargas-Neumann, Blondet, Iwaki, 2010). Through the revision of the literature, a few research projects have been identified with a focus on the specified adobe monument or archaeological site in the seismic-prone regions (EERI, 2004;Maïni, 2004;Manafpour, 2003;Vargas-Neumann et al, 2011;.…”
Section: Third Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have carried out research on the concepts and principles of site protection to form international guidelines for the preservation, protection, and utilization of earthen architectural sites, and such research achievements have been widely applied to immovable cultural heritage sites throughout the world [8]. Furthermore, the structural design and seismic protection of earthen sites were researched to reveal the seismic characteristics and damage behaviors of earthen sites, forming the methods of site assessment and reinforcement [9,10]. The technology of the surface anti-weathering of earthen sites was researched, and soft cover against weathering was promoted [11].…”
Section: Introductionmentioning
confidence: 99%